Gianotti-Crosti syndrome with palmo-plantar bullous lesions. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
Gianotti-Crosti syndrome in its original description is characterized by coarse, close but not confluent papular lesions of the limbs, buttocks and face saving the trunk, linked to hepatitis B virus infection. The disciples of Gianotti (1) in a retrospective analysis of 308 cases concluded that numerous viruses may be responsible for the syndrome; recently, molluscum contagiosum virus also seems to be responsible (2). It has also been asserted (1) that there is no difference between the forms due to hepatitis virus and the others and that there are no significant differences between papular forms and papulo-vesicular forms. The latter are more frequent, often itchy and are not associate with hepatitis or capillary fragility; they last longer and can recur. The unusual presence of blisters in the actual case is due to the violence of phlogosis and the thickness of the horny layer in the palmo-plantar area.